Answer:
x = 5
Explanation:
-7(-1 + 3x) - 7x = -133
According to PEMDAS, we want to look at the parentheses first.
In this case, the expression within the parentheses is already fully simplified. There are no exponents, so we will move on to multiplication. Distribute the -7 across the parentheses.
7 - 21x - 7x = -133
Now combine the variables.
-21x - 7x + 7 = -133
-28x + 7 = -133
Now combine the constants.
-28x = -140
isolate x by dividing both sides by -28.
x = 5
Check this by plugging this value back into the original equation.
-7(-1 + 3(5)) - 7(5) = -133
Follow PEMDAS (the underlined values are the components we handled)
-7(-1 + 15) - 7(5) = -133
-7(14) - 7(5) = -133
-98 - 35) = -133
-133 = - 133
Your answer is correct.
Hope this helps!